A Concise One‐Pot Organo‐ and Biocatalyzed Preparation of Enantiopure Hexahydrofuro[2, 3‐b]furan‐3‐ol: An Approach to the Synthesis of HIV Protease Inhibitors. Issue 10 (15th March 2016) - Kanemitsu, Takuya; Inoue, Mizuho; Yoshimura, Nono; Yoneyama, Kazutoshi; Watarai, Rie; Miyazaki, Michiko; Odanaka, Yuki; Nagata, Kazuhiro; Itoh, Takashi
Abstract: A simple and efficient one‐pot synthesis of enantiopure hexahydrofuro[2, 3‐ b ]furan‐3‐ol, a crucial component of HIV‐1 protease inhibitors, was developed. The one‐pot process involves an organocatalytic condensation followed by an enzymatic optical resolution. The condensation of 1, 2‐dihydrofuran and glycolaldehyde was achieved using Schreiner's thiourea catalyst (1 mol‐%). A subsequent lipase‐catalyzed kinetic resolution gave the target alcohol with >99 % ee . To demonstrate the practicality of this method, Darunavir, an HIV‐1 protease inhibitor used to treat multi‐drug‐resistant HIV, was synthesized. Abstract : A simple and efficient one‐pot synthesis of enantiopure hexahydrofuro[2, 3‐ b ]furan‐3‐ol, a component of HIV‐1 protease inhibitors, was developed. The one‐pot process involves an organocatalytic condensation catalyzed by Schreiner's thiourea catalyst (1 mol‐%), followed by a lipase‐catalyzed kinetic resolution to give the target alcohol with >99 % ee .